2010
DOI: 10.1007/s10661-010-1827-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carcinogenic heavy metal levels in Brazilian cigarettes

Abstract: Several studies have associated high cancer incidence with smoking habits. According to IARC, lead (Pb), cadmium (Cd), arsenic (As), nickel (Ni), and chromium (Cr) are carcinogenic to humans. These metals are present in cigarettes and their levels vary according to geographical region of tobacco cultivation, fertilizer treatment, plant variety etc. This study aims to assess these metal levels in cigarettes commercialized in Brazil. Three cigarettes of each 20 different brands were individually weighed, the tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 19 publications
7
29
0
11
Order By: Relevance
“…PY (Pack-Year) smoking index expressed as the number of packs of 20 tobacco cigarettes per day for 1 year, SD standard deviation, ns non-significant (p>0.05) a Significantly different compared with the controls in the same stratum of risk factor group b All types of tobacco consumption (smoking+shisha+chewing) c The blood Cd and Ni levels increase significantly among controls and cases d Former smokers: subjects who smoke between 1 to 18 PY; current smokers: subjects who smoke more than 18 PY However, Collins et al (2002) and Wu et al (2013) found that nasal polyps appears to be affected by certain modifiable extrinsic factors, including cigarette smoking. Several studies reported that tobacco consumption constitutes an important source of chronic exposure to numerous xenobiotics, including heavy metals in particular Cd (IARC 1990;Wadhwa et al 2010;Viana et al 2011;Ashraf 2012). Previously, Cd and Ni exposure via tobacco consumption has been estimated based on the measurements of their concentrations in the blood of smokers compared to nonsmokers Gil et al 2011;Khlifi et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…PY (Pack-Year) smoking index expressed as the number of packs of 20 tobacco cigarettes per day for 1 year, SD standard deviation, ns non-significant (p>0.05) a Significantly different compared with the controls in the same stratum of risk factor group b All types of tobacco consumption (smoking+shisha+chewing) c The blood Cd and Ni levels increase significantly among controls and cases d Former smokers: subjects who smoke between 1 to 18 PY; current smokers: subjects who smoke more than 18 PY However, Collins et al (2002) and Wu et al (2013) found that nasal polyps appears to be affected by certain modifiable extrinsic factors, including cigarette smoking. Several studies reported that tobacco consumption constitutes an important source of chronic exposure to numerous xenobiotics, including heavy metals in particular Cd (IARC 1990;Wadhwa et al 2010;Viana et al 2011;Ashraf 2012). Previously, Cd and Ni exposure via tobacco consumption has been estimated based on the measurements of their concentrations in the blood of smokers compared to nonsmokers Gil et al 2011;Khlifi et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In certain smokeless tobacco (SLT) products, cadmium concentrations have been reported to range between 450 and 1880 ng per gram dry weight Maier et al, 1989;Pappas et al, 2008). In non-combusted cigarette tobacco, cadmium has been reported at concentrations between 100 and 4,950 ng per gram of tobacco (Viana et al, 2011;Westcott and Spincer, 1974;Yue, 1992). And in cigarette MSS, depending on cigarette design and the machine smoking regimen, cadmium concentrations between 1.6 and 222 ng per cigarette have been reported (Counts et al, 2005;IARC, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, univariate analysis suggested that the levels of arsenic are statistically significantly higher in the absence of SHS exposure at home as compared to in the presence of SHS exposure at home (Table 2) for children and adults. These results, given the research findings that arsenic is present in cigarette smoke (Lazarevi c et al 2012, Viana, Garcia, andMenezes-Filho 2011), were totally unexpected. These results can, however, be explained by the racial/ethnic composition (Table 1) of those who had SHS exposure at home and those who did not.…”
Section: Discussionmentioning
confidence: 78%
“…Arsenic has been found to be a constituent in tobacco, the levels of which may vary by plant variety, geographical location of tobacco cultivation, and fertilizer treatment among other factors (Viana, Garcia, and Menezes-Filho 2011). In a study (Lazarevi c et al 2012) that evaluated the levels of arsenic and lead in 617 tobacco samples and 80 samples of cigarettes, the mean level of arsenic found in tobacco and cigarette samples was found to be 0.15 mg/g (<0.02À2.04 mg/g) and 0.11 mg/g (<0.02À0.71 mg/g), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation